2019
DOI: 10.1371/journal.pone.0221058
|View full text |Cite
|
Sign up to set email alerts
|

Relations of advanced glycation endproducts and dicarbonyls with endothelial dysfunction and low-grade inflammation in individuals with end-stage renal disease in the transition to renal replacement therapy: A cross-sectional observational study

Abstract: Background Cardiovascular disease (CVD) related mortality and morbidity are high in end-stage renal disease (ESRD). The pathophysiology of CVD in ESRD may involve non-traditional CVD risk factors, such as accumulation of advanced glycation endproducts (AGEs), dicarbonyls, endothelial dysfunction (ED) and low-grade inflammation (LGI). However, detailed data on the relation of AGEs and dicarbonyls with ED and LGI in ESRD are limited. Methods We examined cross-sectional Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 55 publications
(66 reference statements)
0
26
0
Order By: Relevance
“…It has been described that the plasma concentration in type 2 diabetes patients of 3-DG is 1.37 μ mol/L, of GO 0.74 μ mol/L, and of MGO 0.31 μ mol/L [ 54 ]. In serum of patients with chronic kidney disease, the amounts have been found to be of 1.64 μ mol/L for 3-DG, 1.72 μ mol/L for GO, and 1.08 μ mol/L for MGO [ 55 ]. In peritoneal dialysis fluids, 3-DGal has been detected at a concentration of ≤16 μ mol/L and 3-DG at a concentration of ≤7 μ mol/L [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been described that the plasma concentration in type 2 diabetes patients of 3-DG is 1.37 μ mol/L, of GO 0.74 μ mol/L, and of MGO 0.31 μ mol/L [ 54 ]. In serum of patients with chronic kidney disease, the amounts have been found to be of 1.64 μ mol/L for 3-DG, 1.72 μ mol/L for GO, and 1.08 μ mol/L for MGO [ 55 ]. In peritoneal dialysis fluids, 3-DGal has been detected at a concentration of ≤16 μ mol/L and 3-DG at a concentration of ≤7 μ mol/L [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, we found a notable presence of MG-H1 in the epidermis, which may partly explain this finding. Moreover, previous studies in different body compartments (serum and lens proteins) have shown mixed results [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced glycation end products (AGEs), proinflammatory and pro-oxidative compounds classified as uremic toxins, are produced through the non-enzymatic glycation and oxidation of proteins, lipids, and nucleic acids. Their accumulation in CKD promotes endothelial dysfunction and subsequent diseases [ 115 , 116 , 117 , 118 , 119 , 120 ]. Atherosclerosis, autoimmune disease, diabetes mellitus, and inflammatory diseases are closely linked to the AGE receptor-ligand axis [ 121 , 122 , 123 , 124 ].…”
Section: Transporters and Receptors Of Uremic Toxins In The Endothmentioning
confidence: 99%